Implantación de la contabilidad comercial para la “DISTRIBUIDORA DIMAGO” de la ciudad de Loja, periodo enero – febrero del 2015 - Granda Guachizaca, Cindy Sulay (2016)
This research is titled: IMPLEMENTATION OF ACCOUNTING FOR COMMERCIAL “DISTRIBUTOR DIMAGO” LOJA CITY, PERIOD JANUARY – FEBRUARY 2015. Captured it in order to improve the efficiency of their business operations to solve the lack of an accounting control has not allowed to know its real economic and financial situation in the distributor and for the benefit of its owner the Engineer. Boris Alexander Maza Jara, based on the Regulation of Academic Board of the National University of Loja, prior to obtaining the title of Engineer in Accounting and Auditing CPA. The goals outlined in the development of research, were fulfilled as they allowed us to establish a plan and manual analysis, the implementation of the accounting process, starting with the Initial Inventory, State Initial Situation, General Journal, Major General, Balance Checking and Financial Statements which provide the real economic situation of the company, giving a better view in the short, medium and long term to its owner. The same thing can give way to potential investors to extend their lines of purchases and sales. At the end of the investigation accounting was introduced in the Dimago distributor obtaining the development of real and timely financial statements, as well the importance of continuing running the accounting process with all auxiliary records for buying and selling, the Kardex cards to bring adequate control in the goods, depreciation of assets, all this help so that the results are reliable in making decisions for the growth of the distributor.